PHYTOCHEMICAL SCREENING AND QUANTIFICATION OF PLANT METABOLITES IN THE STEM EXTRACT OF TINOSPORA CORDIFOLIA (WILLD.) MIERS - M. AMUDHA; DR.S. KRISHNAKUMARI (International Journal of Pharma and Bio Sciences, 2016)
Tinospora cordifolia is an annual or perennial Ayurvedic plant which is still used in several traditional medicines to cure various diseases. Qualitative phytochemical screening and Quantification of metabolites were carried out in the present study. Five solvents: water, ethanol, methanol, acetone and petroleum ether were used to obtain the extracts of stem. The shade dried powdered stem material was subjected to Soxhlet extraction using different solvents and hot water extraction. The resultant extraction was subjected to screening of phytochemicals and estimation of metabolites using standard procedure. The stem extracts of varied solvents and aqueous extract were analysed and tabulated with the presence and absence of phytoconstituents. Further hot aqueous stem extract showed good amount of nutrients and medicinal properties based on the quantitative determination of primary and secondary metabolites. Thus the present findings suggest that the stem contains more active constituents and could be used in pharmaceuticals industries for the production of making quality products.